Analysis of External Factors on MSME Performance Through Internal Factors (Case Study on Embroidery MSMEs in Mojokerto District) - Rachmawati, Eny; Rizkawati, Nidya; Abdillah, Adil (Jurnal Multidisiplin Madani, 2023)
This research was conducted to test the influence of external factors on the performance of MSMEs through internal factors with a case study carried out on embroidery MSMEs in Mojokerto Regency. This research uses external factor variables consisting of aspects of government policy and aspects of the role of related institutions as exogenous variables. The mediating variables in this research are internal factors which include capital aspects, market and marketing aspects and human resource aspects. Meanwhile, the endogenous variable in this research is the Performance of Embroidery MSMEs in Mojokerto Regency. The research population used was embroidery MSMEs in Mojokerto Regency which are members of the Mojokerto Regency Embroidery Entrepreneurs Association (ASPENDIR) totaling 60 embroidery MSMEs in Pasuruan Regency with the sampling method used was the census method. External factors also have a significant influence and are positively related to the internal factors of embroidery MSMEs in Pasuruan Regency. Internal factors have a significant influence and are negatively related to the performance of Embroidery MSMEs in Mojokerto Regency. Meanwhile, the influence of external factors on the performance of MSMEs through Internal Factors is significant but has a negative relationship